(untitled) (Al-Academy, 2018)
The present research deals with the study of the symmetries of the design of interior spaces in fast food restaurants in terms of formality as it is an important element and plays a direct role in the spatial configuration, which is designed in both of its performance, aesthetic and expressive aspects. Since the choice of shapes is a complex subject that has many aspects imposed by functional and aesthetic correlations, the problem of the research is represented by the following question: (To what extent can the symmetries of the interior design be used in the spaces of fast food restaurants?) The research acquires its importance by contributing to the addition of knowledge to researchers, scholars, companies and the specialized public institutions and those relevant in the field of interior design to benefit from them to develop fast food restaurants through awareness of the role of formal symmetries to achieve the performance and aesthetic aspects of users of these spaces of workers, visitors and tourists. The objective of the research is to identify the formal symmetries in the designs of the interior spaces of fast food restaurants.The theoretical framework has been defined by two sections: the first of which is "the formal symmetries in the design of interior spaces", while the second section includes "the interior design of fast food restaurants". The results and conclusions of the research have been reached through the approved research procedures and methodology. The most important conclusions are: 1 - There is a clear absence of golden proportions in the formal symmetries of the dimensions of some walls and windows. 2 - The modular system acts as a proportional system in determining the dimensions of the entrance and areas of movement in the interior spaces of the restaurants and in determining the forms of sitting units, chairs and tables that contribute to the impact on the human psyche to stay for a limited period.